Effect of heat stress on superoxide anion production in native and crossbred cattle under in vitro whole blood culture model. (January 2020) - Verma, Nitika; Alyethodi, Rafeeque R.; Kathuria, Ashima; Alex, Rani; Hussain, Shaziya; Singh, Umesh; Tyagi, S.; Sirohi, Ajveer Singh; Kumar, Sushil; Deb, Rajib; Sengar, Gyanendra S.; Raja, T.V.; et al.
Abstract: Impact of global warming on the dairy industry has gained attention due to huge economic losses through low production and fertility caused by heat stress. Exposure to hyperthermia provokes a series of complex responses in mammals which are been related to morphological and physiological alterations including the production of reactive oxygen species (ROS). A quantitative spectrophotometric based nitroblue tetrazolium (NBT) reduction assay was used to estimate the superoxide anion (O2 − ) level in heat stressed (at 42 °C) whole blood cultures of native and crossbred bulls (Sahiwal and Frieswal), in vitro . The breed effect in the kinetics of O2 − production at different time periods of continual heat stress was analyzed by repeated measures ANOVA. Comparison between different time periods in reference to 37 °C was analyzed by paired t-test. The O2 − level was significantly different (p < 0.05) between cells at 37 °C and 42 °C at different periods of incubation. Kinetics study showed increment of O2 − production on the acute phase of stress followed by a reduction in both Sahiwal and Frieswal breeds. In Sahiwal breed, the inflated superoxide level continued abated till 4 h and raised again at 6 h, while in Frieswal O2 − level reverted to raise sooner with in 2 h of incubation itself. Contrarily, kinetic of O2 − level in plasma showed a significant reduction (p < 0.001) at 30 min of 42 °C incubation followed by increment of O2 − level. Further, the breed variation was significant (p < 0.05) and a significant high reduction of O2 − level was observed in Sahiwal breed. Our finding indicates that, a better and longer O2 − production homeostasis and higher plasma scavenging ability of native breed may be one of the reasons for the higher thermal tolerance of these breeds in tropical climate. Highlights: This study utilizes highly sensitive and easy to perform spectrophotometric NBT assay. Effect of breed and time on heat stressed in vitro whole blood culture model may represents more realistic situation. NBT assay on cells partly indicate evolution of adaptive mechanisms in the Frieswal bulls who are 10 th generation progenies. A longer O2 − homeostasis and better plasma scavenging in native breed may be the reason for their higher thermal tolerance.